Practical Analysis of Tap Water Dissolved Solids Efficient Reduction - Muhammad Imran Majid; Naeem Shahzad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
Water is an essential component in the manufacturing of oral solid dosage forms in the pharmaceutical industry. The objective of the present study is to develop a compact and easy-to-maintain one-platform solution for generating high-purity water with near to zero Total Dissolved Solids (TDS) and low conductivity for pharmaceutical applications. To achieve this objective, different purification methods were explored and integrated into a single platform. The purification process involved the use of Electro-Deionization (EDI) in combination with double-pass Reverse Osmosis (RO), an activated carbon filter, water softeners, and micron filtration. The resource water was carefully selected based on specific criteria to ensure the quality of the final purified water. The developed one-platform solution successfully produced purified water with near to zero TDS and a conductivity level below 1 micro siemens/cm2. The integrated approach involving EDI and double-pass RO, along with supplementary filtration and treatment steps, proved to be highly effective in achieving the desired purity levels. The study demonstrated that the suggested one-platform solution is a reliable and efficient method for the production of high-purity water in the pharmaceutical industry. This system offers an easily maintainable and compact solution, making it suitable for various other industries such as semiconductor manufacturing and electric power generation where purified water with zero TDS is required. By providing a robust water purification process, this solution contributes to enhancing the quality and safety of pharmaceutical products and other critical applications that rely on ultra-pure water.